"Father" of Hong Kong nationalism? A critical review of Wan Chin's city-state theory. Issue 4 (5th October 2015) - Cheung, Tommy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to give a critical review of the City-State Theory by Wan Chin of Hong Kong. Chin is referred to as the "Father of Hong Kong Independence, " and his two books about the City-State Theory of Hong Kong are popular among the netizens in Hong Kong as a new model of Hong Kong-China (People's Republic of China (PRC)), in which Hong Kong is considered a city-state and should be fully segregated from the PRC other than in seeking its help in military and diplomatic functions. This paper will aim to review his works with the view of nationalism and nativism theories. Design/methodology/approach – This paper uses nationalism theories with particular focus on Benedict Anderson's Imagined Communities and theories on American nativism. Then an effort is made to compare these theories against Chin's arguments on his City-State Theory. This paper also compares his theories against China's state-nationalism raised by Professors He and Guo. Findings – This paper concludes that Chin advocates a "Hong Kong Nationalism, " a blend of traditional Chinese culture and moral values (he used the term Huaxia), but with a Western influence, into a typical Hong Kong culture. His theory fits into Anderson's arguments of allowing Hong Kong citizens to imagine Hong Kong as a nation, through the "ramparts" of the city-state. His nativist advocacies also have shown strong nationalistic sentiments. He argues that China should be built in the Hong Kong model before the PRC intervention. Originality/value – Despite his fame, this paper is the first comprehensive academic paper to review Chin's theories. This paper introduced the notion of "ramparts" and how this has become the backbone of Chin's nationalism advocacies.